THE RELATIONSHIP OF EMPLOYEE PERCEPTION ABOUT IMPLEMENTATION OF K3 WITH THE USE OF PPE (PERSONAL PROTECTION EQUIPMENT) - binarti dwi wahyuningsih; Lutfi Wahyuni (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
The use of Personal Protection Equipment (PPE) is the last choice of the method of controlling accident and occupational diseases. Nevertheless, the use of PPE discipline will be critical important for companies and employees to reduce the risk of accidents and occupational diseases. The purpose of of this research is to know the relation of employee perception about implementation of K3 with the use of personal protection equipment (PPE). The design of this research is analytic correlational with cross-sectional aproach 21-27 May 2017. The population this research was employees production unit in UPT. Balai Yasa Surabaya Gubeng. Sample were taken by total sanpling technique as much as 33 respondents. The data were collected with observation for the use of PPE and questionnaires for employee perception about implementation of K3, then tested with a statistical distribution (Crosstab) Chi-Square and are presented in tabular form. The result of the research shown of 33 respondents were 17 respondents (51,5%) who has a positive perception mostly has the use of PPE on the good level and 9 respondents (27,3%) has the use of PPE in the sufficient level. Based on this research gotten a statistical result with a value of the Ï value = 23,209 with Ï= 0,000 or É‘ < 0,05 with this it can be concluded that there is a sognificant relationship between employee perception about implementation of K3 with the use of PPE. Based on this research are expected employees to improve discipline in the use of PPE (Personal Protection Equipment) in complete especially the use of mask and gloves